2007
DOI: 10.1007/s00280-007-0469-9
|View full text |Cite
|
Sign up to set email alerts
|

Alemtuzumab plus CHOP as front-line chemotherapy for patients with peripheral T-cell lymphomas: a phase II study

Abstract: The alemtuzumab plus CHOP chemotherapy seemed to produce active antitumor activity in terms of the complete response rates in patients with PTCLs. However, since high infectious and hematologic toxicities were observed, careful monitoring and early treatment are needed to prevent treatment-related mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
2
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(47 citation statements)
references
References 18 publications
3
38
2
4
Order By: Relevance
“…Although our ORR seems similar to other studies using various regimen [15-20, 23-27, 42-44, 53], the result needs to be interpreted carefully because other similar studies using alemtuzumab-CHOP have the highest number of PTCL, NOS cases among their study subjects [42,43], whereas no PTCL, NOS subject was recruited into our study during the study period.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Although our ORR seems similar to other studies using various regimen [15-20, 23-27, 42-44, 53], the result needs to be interpreted carefully because other similar studies using alemtuzumab-CHOP have the highest number of PTCL, NOS cases among their study subjects [42,43], whereas no PTCL, NOS subject was recruited into our study during the study period.…”
Section: Discussionsupporting
confidence: 79%
“…In one of the alemtuzumab-CHOP trials of using oral acyclovir 400 mg twice daily as CMV prophylaxis, 15 episodes of CMV reactivation were observed in the total of 24 subjects [43]. Another alemtuzumab-CHOP study which used oral acyclovir 600 mg twice daily had CMV reactivation in five out of the total of 20 patients [42]. Our study used lower dose of oral acyclovir, which was 200 mg thrice daily.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…26 AL was given in combination with CHOP at various schedules and doses; the achievement of CR varied from 65 to 70%, although with a quite limited advantage in terms of EFS. 6,7,8 Despite the absence of phase III trials, the consolidation of response with autoSCT is commonly employed in the clinical practice and the evidence is mostly derived from phase II studies. The most recent prospective trials of up-front autoSCT reported a favorable outcome with 3-year PFS and OS ranging from 36 to 48% and from 48 to 56%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, the 2-year EFS was not improved, suggesting that a consolidation was probably required. 6,7,8 Therapy intensification with up-front autologous stem cell transplantation (autoSCT) was explored in phase II studies and resulted in a 3-year EFS ranging from 30 to 50%. 9,10,11,12 Recently, the Nordic Lymphoma group reported the results of up-front autoSCT following six courses of CHOEP-14.…”
Section: Intensified Chemo-immunotherapy With or Without Stem Cell Trmentioning
confidence: 99%